The balint method online: Past, pandemic and future. (November 2022) - Lichtenstein, Albert; Buck, Lisa; Nease, Donald
The Balint Method has been used worldwide since Michael and Enid Balint developed it in the 1950s. Even with the proliferation of Balint groups there were still doctors and other clinicians who did not have local access. The online format was developed to provide Balint groups to those individuals. With the pandemic the majority of clinicians were unable to get together in person. The online format provided a lifeline for Balint work. This article provides a short history of the development of Balint online, how the pandemic affected further development, and a summary of what was learned from that experience.